The evolution of technical and technological education in higher education - Mamani Chuquimia, Oscar (2023)
This review article aims to present an overview of the evolution of technical and technological education in higher education, its challenges, opportunities and future perspectives. It examines the historical evolution of technical and technological education, educational models, competencies and skills needed, and discusses current trends that are changing the educational landscape. The method used was the analysis and synthesis of information from various academic sources and specialized literature. It is concluded that it is of utmost importance for technical and technological education to focus on the development of technical, technological and socioemotional competencies to face the challenges of today's labor market and thus reduce wage inequality and poverty in modern societies, with close collaboration between academia, industry and government, to improve the quality and relevance of technical and technological education in today's world.